1997
DOI: 10.1111/j.1600-0404.1997.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic analytical parameters as the predictive factors for 30-day case fatality rate in stroke

Abstract: In a prospective population-based study, analyses were performed to evaluate the 30-day case fatality in stroke as related to the following factors: hematocrit (HCT), hemoglobin (Hgb), red blood cells (RBC), mean cell volume (MCV), platelet count, erythrocyte sedimentation rate (ESR), white blood cells (WBC) and glucose concentration. We studied 345 patients with stroke, 170 men and 175 women, mean age 68.4 +/- 14.2 years, admitted within 72 h of stroke onset. Patients who died had significantly higher mean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 37 publications
1
35
1
7
Order By: Relevance
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…There were also 2 studies that did not state the design 21, 26. There was a high degree of diversity in geographic location, with cohorts from Germany,8, 19, 25 Switzerland,16, 20 the United States,18, 24 the People's Republic of China,2, 22 Canada,23, 28 India,6 Israel,10 the Republic of Korea,9 Denmark,21 Taiwan,17 the United Kingdom,26 and Poland 7. In addition, 2 studies were conducted across multiple countries 1, 27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations